Investigating the Language Learning Strategies (LLS) Used By Students of English Practicum Class at University of Medan Area - Muhammad Muslim Nasution; Rizky Vita Losi (JOLADU: Journal of Language Education, 2023)
This research purposed to investigate the EFL learners on the using of Language Learning Strategies (LLS) in learning English. This research aimed to find out the level of using LLS and identify the most and least used strategy by EFL learners at University of Medan Area. This research employed a descriptive quantitative method. The total sampling technique was applied to all participants of EFL students who enrolled English practicum class in 2023-2024. The data were gathered through the Strategy Inventory for Language Learning (SILL) questionnaire version 7.0 developed by Oxford and was administered to all 50 EFL students. SILL consists of 50 statements which have six categories, as follow: Memory, Cognitive, Compensation, Metacognitive, Affective, and Social strategies. The data were analyzed through Microsoft Excel and SPSS version 25. The data result revealed that Compensation strategy (M=4.13) was the most often used by the EFL students, while Memory strategy (M=3.18) was the least used by them. In the end, the EFL learners who used Strategy Inventory for Language Learning (SILL) reached the medium and high level in this research.